Path Integration Changes as a Cognitive Marker for Vascular Cognitive Impairment?—A Pilot Study - Lowry, Ellen; Puthusseryppady, Vaisakh; Coughlan, Gillian; Jeffs, Stephen; Hornberger, Michael (Frontiers in Human Neuroscience, 2020)
Path integration spatial navigation processes are emerging as promising cognitive markers for prodromal and clinical Alzheimer’s disease (AD). However, such path integration changes have been less explored in Vascular Cognitive Impairment (VCI), despite neurovascular change being a major contributing factor to dementia and potentially AD. In particular, the sensitivity and specificity of path integration impairments in VCI compared to AD is unclear. In the current pilot study, we explore path integration performance in early-stage AD and VCI patient groups and hypothesize that: (i) medial parietal mediated egocentric processes will be more affected in VCI; and (ii) medial temporal mediated allocentric processes will be more affected in AD. This cross-sectional study included early-stage VCI patients (n = 9), AD patients (n = 10) and healthy age-matched controls (n = 20). All participants underwent extensive neuropsychological testing, as well as spatial navigation testing. The spatial navigation tests included the virtual reality “Supermarket” task assessing egocentric (body-based) and allocentric (map-based) navigation as well as the “Clock Orientation” test assessing egocentric and path integration processes. Results showed that egocentric integration processes are only impaired in VCI, potentially distinguishing it from AD. However, in contrast to our prediction, allocentric integration was not more impaired in AD compared to VCI. These preliminary findings suggest limited specificity of allocentric integration deficits between VCI and AD. By contrast, egocentric path integration deficits emerge as more specific to VCI, potentially allowing for more specific diagnostic and treatment outcome measures for vascular impairment in dementia.